Usia Menopause Alami Dan Menganalisis Hubungannya Terhadap Jumlah Paritas Pada Wanita - Sri Wijayanti; Dewi Putri (STIKES Columbia Asia Medan, 2023)
Menopause means the cessation of the menstrual cycle forever for women who previously had menstruation every month, which was caused by the number of follicles experiencing atresia continuing to increase, until there were no more follicles available, and in the last 12 months experiencing aminorhoea, and not caused by a pathological condition (Fitri, 2017). Menopause is a condition where a woman no longer experiences menstruation which occurs between the ages of 50 and 59 years (Harlow, 2012).